TANGGUNG JAWAB NEGARA DALAM PEMENUHAN HAK ATAS KESEMPATAN BERUSAHA BAGI FAKIR MISKIN DI MASA PANDEMI CORONA VIRUS DISEASE-19 - Glien Excell Julio Marshanda; Zulfikar Jayakusuma; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The state has an obligation to prosper all its citizens from poverty as mandated in thePreamble of the 1945 Constitution of the Republic of Indonesia, including caring for thepoor. As stated in Article 34 paragraph (1) of the 1945 Constitution which states that "Thepoor and abandoned children are cared for by the state". Efforts to respect, protect and fulfillthe right to basic needs are state obligations that are carried out in order to be free fromconditions of destitution and poverty. These efforts must be made by the state as a top priorityin national development, including for the welfare of the poor.The type of research used is normative research, or it can be called library research,namely conducting a study of the applicable law and how it is in reality in society throughanalysis of library data. Data collection techniques in this research using literature studiesby analyzing books, laws and regulations to policy-related studies and other literature.From the results of the study, it is concluded that, first, the State, in this case theGovernment of Indonesia, is responsible for fulfilling the right to obtain businessopportunities for the poor in accordance with Article 17 of Law Number 13 of 2011concerning Handling the Poor despite the Covid-19 Pandemic, Second, the Governmentfaces various obstacles in fulfilling business opportunities, including restrictions due to theCOVID-19 Pandemic itself, the large number of people who work in the non-formal sector,poor data collection on recipients of social assistance, socialization that is not optimal andcases of corruption by officials against existing assistance.Keywords: State Responsibility – Poverty – Covid-19 Pandemic